1981
DOI: 10.1002/jez.1402180224
|View full text |Cite
|
Sign up to set email alerts
|

A note on the inhibition of in vitro meiotic maturation of mammalian oocytes by dibutyryl cyclic AMP

Abstract: Cytogenetic data are presented which indicate species differences in the response of oocytes maturing in vitro in the presence of dibutyryl cyclic AMP (dbcAMP). Inhibition of ewe oocyte maturation was noted at germinal vesicle, MI, and MI1 in the presence of 25-750 pg/ml of dbcAMP. Cow oocytes were primarily affected at MI and MI1 by similar concentrations, and only 750 pglml delayed golden hamster oocytes at these stages. These findings highlight the variability between the responses of the oocytes of these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…In addition to the different effects of the cAMP‐elevating agents in different culture media, cAMP itself was reported as being “ineffective, inhibitory or stimulatory depending on the species” [ewe, cow, monkey, and human oocytes were tested by Jagiello et al (1975)]. In other studies, mouse and rat oocyte meiosis was almost totally inhibited by dbcAMP at 100 µg/ml (Stern and Wassarman, 1974; Magnusson and Hillensjö, 1977), while a concentration of 750 µg/ml was necessary to increase the percentage of bovine oocytes remaining at the GV stage (Jagiello et al, 1981).…”
Section: Role Of Camp In the Control Of Bovine Oocyte Meiosismentioning
confidence: 99%
“…In addition to the different effects of the cAMP‐elevating agents in different culture media, cAMP itself was reported as being “ineffective, inhibitory or stimulatory depending on the species” [ewe, cow, monkey, and human oocytes were tested by Jagiello et al (1975)]. In other studies, mouse and rat oocyte meiosis was almost totally inhibited by dbcAMP at 100 µg/ml (Stern and Wassarman, 1974; Magnusson and Hillensjö, 1977), while a concentration of 750 µg/ml was necessary to increase the percentage of bovine oocytes remaining at the GV stage (Jagiello et al, 1981).…”
Section: Role Of Camp In the Control Of Bovine Oocyte Meiosismentioning
confidence: 99%
“…However, higher concentrations of the cAMP-elevating agents were necessary to transiently increase the percentage of bovine oocytes remaining at the GV stage after in vitro culture (Jagiello et al, 1981, Sirard & First, 1988 compared to concentrations that were effective in rodent oocytes. Since AC was detected on their plasma membrane (Kuyt et al, 1988), it was concluded that bovine oocytes could possibly generate sufficient amount of cAMP for meiotic arrest.…”
Section: Role Of Camp In the Control Of Bovine Oocyte Meiosismentioning
confidence: 90%
“…Similar to bovine oocytes, meiotic resumption was only partially inhibited by cAMP-elevating agents in ovine oocytes (Jagiello et al, 1981). Ovine oocytes possess an AC enzyme as cholera toxin, a Gs activator, stimulated cAMP synthesis in isolated sheep oocytes (Crosby et al, 1985).…”
Section: Role Of Camp Mapk In the Control Of Meiosis In Ovine Oocytesmentioning
confidence: 94%
See 1 more Smart Citation
“…The role of cyclic adenosine monophosphate (cAMP) in the maintenance of meiotic arrest has been well documented in mouse and rat oocytes (Dekel and Beers, 1978;Schultz, 1988 (Jagiello et al, 1981;Racowsky, 1985b;Moor, 1988 (Sirard and First, 1988). Also in sheep, GVBD occurs in vitro even in the presence of a cAMP-elevating agent (Moor and Heslop, 1981;Crosby et al, 1985; Moor and Seamark, 1986).…”
Section: Introductionmentioning
confidence: 99%